EVALUATION DES PERTES EN GRAINS DE MIL DUES AUX INSECTES - Békoye, Béninga Marboua; Dadié, Aclé (European Scientific Journal, ESJ, 2015)
Field experiments were conducted to determine millet grain losses due to stem boers and panicle insects during two consecutive years at Ferkessedougou Research Station in Côte d’Ivoire. Damages due to stem borers ranged from 45.3 to 51.7%. Sesamia calamistis and Eldana saccharina were the two dominant stem borers species. Acigona ignefusalis incidence on studied plots was very low so that this insect could be considered as a minor pest. Panicle insects caused valuable damage and gave 58.2% of grain losses. Grain sucking insects were the dominant species causing panicle damages.